By-laws of the strong - man lodge, No 53, of ancient free and accepted Masons, constituted by charter granted by the grand Lodge of England. Bearing date the 2nd day of February, 1734: Now held at the Falcon Tavern, Fetter Lane (Pollett, 1854)
With: Constitutions of the antient fraternity of free and accepted masons.